Typology of Listening in the Qur’an: An Analytical Study of M. Quraish Shihab’s Tafsir al-Mishbah - Hidayah, Rohmatun Nurul; Sumbulah, Umi; Hasanah, Mamluatul; Widodo, Arif; Chebaiki, Hana (Al-Ulum, 2025)
This study aims to explore the typology of “listening” in the Qur’an as interpreted in Tafsir al-Mishbah by M. Quraish Shihab. Employing a qualitative library research design with a descriptive–analytical approach, this study examines Qur’anic verses discussed in Tafsir al-Mishbah as its primary data sources. Data analysis follows the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that Tafsir al-Mishbah identifies five typologies of listening: (1) physical listening, understood as a biological function and a sign of existence; (2) attentive listening, reflecting spiritual and intellectual awareness; (3) listening in the sense of granting or responding to supplications, which underscores God’s active responsiveness to human prayers; (4) listening with a positive response, signifying obedience, acceptance, and faith; and (5) listening with a negative response, which represents rejection and defiance of truth. These findings affirm that the Qur’anic concept of istimāʿ, as interpreted by Quraish Shihab, extends beyond physical activity and embodies deeper dimensions of consciousness, intention, and moral orientation.